(untitled) (Third Sector Social Economic Review, 2025)
Rising global income inequality, economic vulnerability and technological developments have put the importance of social protection mechanisms on the agenda more than ever before. The purpose of social protection spending is to increase social welfare and reduce inequalities in income distribution by supporting the most vulnerable segments of society. It is argued that a fair distribution of income brings benefits to society. One of these benefits is to ensure sustainable development and social equity. In an economy where income is more equitably distributed, poverty is expected to decrease, health and nutritional conditions will improve, crime rates will decrease, social cohesion will be ensured and living conditions will improve. Moreover, regulating income distribution is now accepted as one of the reasons for government intervention in the economy. One of the instruments used by the state for this purpose is social protection expenditure. Therefore, knowing the impact of social protection expenditure on income distribution is an important issue to guide policy makers. Therefore, this study aims to determine the impact of social protection expenditure on income distribution. The study is based on a panel data analysis using annual data for 33 European Union (EU) Member States and Turkey for the period 2010-2021. The study finds that increasing social protection expenditure reduces income inequality.